Abstract 019: Effective Diagnostic Testing For Uncommon Etiologies Of Venous Pulsatile Tinnitus - Sivani Lingam; Aaron Brake; Vince Galate; Robert Turner; Michael G Abraham (Stroke: Vascular and Interventional Neurology, 2023)
Introduction Pulsatile Tinnitus (PT) is a rhythmic sound in the ears. It can be incapacitating and is even associated with depression and suicidal ideationi. The etiology of PT can be grouped into vascular and non‐vascular causes. ii,iii While prominent venous structures may be believed to be the underlying cause of PT, interventions on these structures do not always result in symptom resolution. Successful treatment is contingent on correctly identifying culpable vascular targets. In this case series, we report 4 cases of pulsatile tinnitus that were successfully treated with endovascular intervention. Methods Retrospective chart review of patients who presented with symptoms of pulsatile tinnitus who were found to have symptoms that resolved on balloon‐occlusion‐testing of various cerebral veins. Results Case 1 A 42‐year‐old woman was referred for right‐sided PT which affected her sleep and quality of life. The initial venogram showed a right internal jugular (IJ) vein diverticulum, which was subsequently coiled. This resulted in a transient improvement in tinnitus. However, her symptoms returned within a few weeks and a repeat venogram showed an enlarged right MEV. She elected to undergo right MEV coil embolization. Two weeks post‐op she noted an improvement of her symptoms, with near resolution. On follow‐up exams, when she applied pressure on her right occipital groove, the tinnitus diminished. Under ultrasound guidance, her PT disappeared when the posterior auricular vein collapsed under applied pressure and returned when the pressure was released. For management she underwent coil embolization of the right occipital vein, as this was the vessel the posterior auricular vein was draining into. Following this intervention her tinnitus resolved. Case 2 A 73‐year‐old male was referred for bilateral pulsatile tinnitus. Initially, he underwent stent‐assisted coiling of a high‐riding jugular bulb with no change in symptoms. During a diagnostic venogram, a balloon‐occlusion test (BOT) of the right mastoid emissary vein (MEV) was performed. Following testing, he reported improved tinnitus. He underwent coil embolization of the right MEV which led to complete resolution of right‐sided PT. Case 3 A 50‐year‐old female was referred for evaluation of right‐sided PT. Catheter venography showed an enlarged right posterior condylar vein (PCV) and right IJ stenosis. Balloon occlusion test (BOT) of the PCV demonstrated improvement in PT. She underwent stent‐assisted coil embolization of the PCV and stenting of her IJ with resolution of her tinnitus. Case 4 A 56‐year‐old female was seen for left‐sided PT, ear fullness, and reduced hearing. A CT venogram revealed left IJ stenosis. Catheter venography showed minimal left IJ stenosis, but a dilated left MEV, measuring 7.31 mm in its widest dimension). BOT of the left MEV resulted in improvement in symptoms. She is scheduled for left MEV coil embolization. Conclusion In this report, we demonstrate 4 cases where abnormal venous structures were the suspected cause of tinnitus based on pre‐treatment occlusion testing. The 3 individuals who have undergone coil embolization of anomalous venous structures have experienced resolution of PT. Balloon occlusion is a useful diagnostic test for therapeutic targeting of abnormal venous etiologies of PT.